Life Skills Approach to Education: Role of the English Classroom - Kohli, Dr. Jyoti (Voices of Teachers and Teacher Educators, 2022)
As is widely recognised, there is a need for life skills education in the light of the demands being made on individuals owing to changed social realities. It is imperative that schools act as sites for engagement with skills that help the contemporary youth to cope with these challenging demands successfully. This paper delineates the concept of and the need for life skills. While outlining the need for developing life skills in the contemporary school going population, this paper suggests a way forward through adopting the life skills approach to education with the help of an illustrative example.